Universally composable secure multiparty computation protocol with fairness - You-liang TIAN; Chang-gen PENG; Jian-feng MA; Hui LIN; Kai YANG (Tongxin xuebao)
The fair problem of secure multiparty computation protocol was investigated in the universally composable framework. A fair secure multiparty computation model with ideal functionalities was firstly formulated such as a fair secure multiparty addition computation and a fair secure multiparty multiplicative computation. Next a fair addition computation protocol and a fair multiplicative computation protocol based on the bilinear paring and the ideal functionality of a commitment scheme was proposed. The proposed protocols can securely realize their ideal functionalities in the hybrid model respectively. Finally, analysis show that these schemes are effective, and it can be more applicable in special situation.